Business Mathematics - Clendenen, Gary; Salzman, Stanley A. (Pearson, 2019)
Business Mathematics teaches the mathematical skills you need for success in business using current issues and pragmatic business scenarios in companies like Starbucks, Bank of America, REI and Apple. These are used throughout each chapter in examples, discussions, exercises and case studies. The authors emphasize business concepts and situations that require a mathematical solution and place every concept in context with relevant examples. The 14th Edition is revised significantly to improve discussions and make the material more meaningful. It is packed with data, examples, graphs, photographs and case studies that demonstrate relevance as it teaches you to interpret data and information. A global perspective is emphasized through examples and exercises that highlight issues in other countries